Organizational alignment using the balance scorecard approach: Case study of a Malaysian government-linked company / Hazeline Ayoup - Ayoup, Hazeline (Institute of Graduate Studies, UiTM, 2016)
The Balanced Scorecard (BSC) constitutes one of the most popular performance measurement systems for organizations. Used solely as a performance measurement system, the BSC highlighted a serious setback: inability of the traditional management systems to link a company’s longterm vision with its short-term strategies. Premised on this deficiency, the BSC application has been further innovated to include using it as an organizational alignment tool. Specifically, the strategic use of BSC as an organizational alignment tool has been proposed by Kaplan and Norton in their 2006’s book Alignment: Using BSC to Create Corporate Synergies. Despite the detail implementation framework outlined in their book, there has been very limited literature written by previous researchers or practitioners to implicate the usage of BSC as an alignment tool. Most works on BSC were based mainly on its role as a performance measurement tool or premised on limited, superficial and generic data. The present study examines the use of BSC as an organizational alignment tool in a large government-linked company (GLC) in Malaysia. To be named as ATB, the case study company was one of the pioneer companies to implement BSC in this country way back in 1996. The use of BSC as an alignment tool became prominent for ATB when the “GLC Transformation Programme” was introduced by the government and came into effect in 2006. This study demonstrates how ATB uses the BSC to create organizational alignment and addresses organizational issues faced by the company in the process. Data for this study were gathered through interviews, analysis of documents, observations and a survey to the company’s employees…